Upaya Meningkatkan Daya Saing UMKM di Era Digitalisasi Bisnis - Yuniar, Eka; Andriyanto, Dicky; Resya, Fachmi; Fidiastutik Wijaya, Dwi Indriani; Yudhistira, Prilinaya; Mujiono, Mujiono; Qori'ah, Maria (Lembaga Dongan Dosen, 2025)
A Small Medium Enterprise sector, as the main pillar of business in Indonesia, has a significant impact on the economic development of the micro and medium sectors. The existence of Small Medium Enterprise must receive attention and an improvement in business management quality so that they become more competitive and open up job opportunities for the surrounding environment of Small Medium Enterprise. One of the weaknesses mostly experienced by Small Medium Enterprise actors is the lack of business management for their operations because the business model that has been applied so far is traditional, which emphasizes revenue generation alone. Therefore, there is a need for socialization of a better and more comprehensive business management model, namely the business model canvas. The community service activity was organized in the form of a seminar, and participants were equipped with methods to implement the business model canvas. The participants were enthusiastic and active throughout the event, and it is hoped that they gained additional insights to run their businesses